Isolation and identification of potentially pathogenic free-living amoeba in dental-unit water samples. (28th June 2022) - Khatoonaki, Hadi; Solhjoo, Kavous; Rezanezhad, Hassan; Armand, Belal; Abdoli, Amir; Taghipour, Ali
Abstract: Although the presence of free-living amoebae (FLAs) in various water sources has been reported, few studies have been surveyed on their abundance in medical-unit and dental-unit water samples. The current study aimed to identify morphological and molecular characteristics of FLA isolates in the water samples of the dental unit in Iran. A total of 232 water samples were collected from 17 dental units. Then, filtration and cultivation were conducted on a non-nutrient agar (NNA) medium. Also, polymerase chain reaction (PCR) assay and sequencing were performed by using the genus/species-specific primers plus a common primer set on positive samples. One hundred and sixty-six samples were positive for FLA by the microscopic method, whereas 114 samples were positive by the molecular method with a common primer set. Considering the PCR assay with genus/species-specific primers, 23.27% (54/232) samples were identified as Acanthamoeba spp. (belonging to T4 genotype), 36.63% (85/232) as Vermamoeba vermiformis, and 1.72% (4/232) as Vahlkampfiidae family ( Naegleria lovaniensis ). These results highlight a need to improve filtration systems in dental units and periodic screenings for FLA in dental-unit water. HIGHLIGHTS: Among 232 water samples of the dental unit, 166 samples were positive for FLA by the microscopic method, whereas 114 samples were positive by the molecular method with a common primer set. Considering the PCR, 23.27% (54/232) samples were identified as Acanthamoeba spp. (belonging to T4 genotype), 36.63% (85/232) as Vermamoeba vermiformis, and 1.72% (4/232) as Vahlkampfiidae family ( Naegleria lovaniensis ). Graphical Abstract